Horror and the horror film - Kawin, Bruce F. (London : Anthem Press, 2012)
Horror films can be profound fables of human nature and important works of art, yet many people dismiss them out of hand. {u0091}Horror and the Horror Film{u0092} conveys a mature appreciation for horror films along with a comprehensive view of their narrative strategies, their relations to reality and fantasy and their cinematic power. The volume covers the horror film and its subgenres {u0096} such as the vampire movie {u0096} from 1896 to the present. It covers the entire genre by considering every kind of monster in it, including the human.
Title from publisher's bibliographic system (viewed on 08 Oct 2015).